2018
DOI: 10.1145/3186677
|View full text |Cite
|
Sign up to set email alerts
|

Creation, curation, and classification: Mario Klingemann and Emily L. Spratt in conversation

Abstract: Computer-generated art has long challenged traditional notions of the role of the artist and the curator in the creative process. In the age of machine learning these philosophical conceptions require even further consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The art exhibition setting also provided opportunities for curatorial interventions that contributed to shape receptions of the objects exhibited; interventions that both art and development communities recognize as imperative for positive AI-generated art reception (Spratt, 2018: 41). Gangadharbatla (2021) has experimentally shown that the information provided to viewers about AI-generated pictures impacts on their perception.…”
Section: Identifying the Lovelace Effect: The Case Of Aicanmentioning
confidence: 99%
“…The art exhibition setting also provided opportunities for curatorial interventions that contributed to shape receptions of the objects exhibited; interventions that both art and development communities recognize as imperative for positive AI-generated art reception (Spratt, 2018: 41). Gangadharbatla (2021) has experimentally shown that the information provided to viewers about AI-generated pictures impacts on their perception.…”
Section: Identifying the Lovelace Effect: The Case Of Aicanmentioning
confidence: 99%
“…The term "engineer" is again borrowed from Lévi-Strauss and does not imply that these artists are trained as engineers or that engineering precedes artistic objectives. Mario Klingemann, for example, is an exemplar for the engineer in AI art, though he does not have a formal training in software engineering [23]. Despite this, Klingemann's work is technically as well as aesthetically masterful.…”
Section: <1> the Engineersmentioning
confidence: 99%